Coagulase-negative staphylococci in multiple blood cultures: strain relatedness and determinants of same-strain bacteremia. - Khatib, R (1995)
The frequency of strain relatedness was determined among randomly selected patients with coagulase-negative staphylococcal infections as determined in multiple blood cultures by plasmid typing, determination of species, and antibiotyping. Strain relatedness was demonstrated in 21 of 47 episodes of bacteremia (44.7%) among 34 patients, with a similar percentage among patients with two or one positive blood culture in 24 h (14 of 30 [46.7%] versus 7 of 17 [41.2%], respectively). Same-strain bacteremia was more frequent in cases of infection among patients with a corresponding fever (15 of 21 [71.4%]), among patients infected with organisms from an identifiable source (7 of 9 [77.8%]) and with non-Staphylococcus epidermidis species (9 of 11 [81.8%]), and among patients with nosocomially acquired infections (18 of 36 [50%]). Comparing episodes with or without strain relatedness, no difference was noted in the time to growth (2.1 +/- 1.4 versus 1.9 +/- 0.9 days, respectively), in bacterial growth in two culture bottles (5 of 14 [35.7%] versus 8 of 24 [33.3%], respectively), and in the presence of additional negative blood cultures (9 of 21 [42.9%] versus 11 of 26 [42.3%], respectively). The antibiotypes of all related strains and 7 of 44 (15.9%) unrelated pairs were identical. These findings demonstrate that coagulase-negative staphylococci from multiple blood cultures are frequently unrelated, suggesting a high prevalence of contamination. In the absence of precise measures for demonstrating strain relatedness, the combination of a clinical assessment with antibiotype determination appears to be a suitable alternative.